Integrated STAT3 and Ikaros Zinc Finger Transcription Factor Activities Regulate Bcl-6 Expression in CD4+ Th Cells - Read, Kaitlin A; Powell, Michael D; Baker, Chandra E; Sreekumar, Bharath K; Ringel-Scaia, Veronica M; Bachus, Holly; Martin, R Emily; Cooley, Ian D; Allen, Irving C; Ballesteros-Tato, Andre; Oestreich, Kenneth J (The Journal of immunology (1950), 2017)
B cell lymphoma-6 (Bcl-6) is a transcriptional repressor that is required for the differentiation of T follicular helper (TFH) cell populations. Currently, the molecular mechanisms underlying the transcriptional regulation of Bcl-6 expression are unclear. In this study, we have identified the Ikaros zinc finger transcription factors Aiolos and Ikaros as novel regulators of Bcl-6. We found that increased expression of Bcl-6 in CD4+ Th cell populations correlated with enhanced enrichment of Aiolos and Ikaros at the Bcl6 promoter. Furthermore, overexpression of Aiolos or Ikaros, but not the related family member Eos, was sufficient to induce Bcl6 promoter activity. Intriguingly, STAT3, a known Bcl-6 transcriptional regulator, physically interacted with Aiolos to form a transcription factor complex capable of inducing the expression of Bcl6 and the TFH-associated cytokine receptor Il6ra. Importantly, in vivo studies revealed that the expression of Aiolos was elevated in Ag-specific TFH cells compared with that observed in non-TFH effector Th cells generated in response to influenza infection. Collectively, these data describe a novel regulatory mechanism through which STAT3 and the Ikaros zinc finger transcription factors Aiolos and Ikaros cooperate to regulate Bcl-6 expression.